LEGAL NIHILISM AS A THREAT TO RUSSIA'S MODERNIZATION (SOCIOLOGICAL ASPECT) - Yu. V. Krasilnikova (Модернизация, инновация, развитие, 2016)
Nihilistic attitude to Law is discussed as one of most serious threats to modernization currently carried out in Russia. «Law nihilism» term is defined, its social forms and influence on political and social development is discussed.